Credit Ratings and Taxes: The Effect of Book–Tax Differences on Ratings Changes - AYERS, BENJAMIN C.; LAPLANTE, STACIE KELLEY; MCGUIRE, SEAN T. (Contemporary Accounting Research, 2010)
This paper examines whether credit analysts utilize the information contained in the difference between book and taxable income in analyzing a firm’s credit risk. Increased book–tax differences may be informative for credit rating agencies as they may signal decreased earnings quality or changes in the firm’s off–balance sheet financing. Results suggest a significant negative association between positive changes in book–tax differences and ratings changes. This evidence is consistent with large positive changes in book–tax differences signaling decreased earnings quality and/or increased off–balance sheet financing. We also find that large negative changes in book–tax differences result in less favorable rating changes, consistent with these changes signaling decreased earnings quality. In additional analyses, we find that the association between changes in book–tax differences and rating changes is attenuated for high–tax‐planning firms (e.g., where book–tax differences more likely reflect tax planning than decreased earnings quality).